The Angola prison seminary : effects of faith-based ministry on identity transformation, desistance, and rehabilitation /: effects of faith-based ministry on identity transformation, desistance, and rehabilitation. (2016) - Hallett, Michael A; Hays, Joshua, 1970-; Johnson, Byron R; Jang, Sung Joon; Duwe, Grant, 1971-
No abstract available